Fixed-dose ultrasound-accelerated thrombolysis for acute pulmonary embolism: short- and long-term outcome data from a single-center study. (3rd May 2023) - Zbinden, S; Voci, D; Kucher, N; Barco, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Data on clinical outcomes after fixed-dosed ultrasound-accelerated thrombolysis (USAT) for acute pulmonary embolism (PE) is still limited, particularly concerning safety and long-term course. Methods: We studied patients with acute PE treated with USAT at a University Hospital between 2018 and 2022. Patients were candidates to USAT if acute PE fulfilled the criteria of high-risk or intermediate-high risk (plus additional markers of clinical severity or early deterioration) as per European guidelines. USAT was given at a standard regimen of 10 mg alteplase/catheter over 15 hours. Early outcomes included: mean pulmonary arterial pressure (mPAP) before and after treatment, National Early Warning Score (NEWS) during USAT; 30-day all-cause death, 30-day hemodynamic decompensation, 30-day PE recurrence, and 30-day major bleeding complications (ISTH definition). Late outcomes were: confirmed CTEPH, persistent post-PE dyspnea, and "post-PE impairment" (PPEI), as defined by the combination of dyspnea with sPAP>35 mm Hg, TAPSE <1.6cm, or RV/RA gradient >36 mmHg, death. Results: We included 161 patients: the mean age was 67.8 (SD 14.6) years and 96 were men. All had acute bilateral PE and were treated with two catheters for a median alteplase dose of 20 mg. All patients received anti-Xa activity-adjusted unfractionated heparin, except one, who received argatroban. mPAP decreased from a mean of 35.6 (SD 9.8) to 25.6 (SD 8.2) mmHg after a 15-hour course of treatment (absolute difference 10.2 mmHg; SD 8.1). The NEWS decreased from a median of 5 (Q1-Q3: 4-6) points before USAT to 3 (Q1-Q3: 2-4) points after USAT. No hemodynamic decompensations were recorded within 30 days of hospitalization. One (0.6%) recurrence of PE within 30 days occurred. Two major bleeding (1.2%), of which one (0.6%) was intracranial and fatal, were observed. No other deaths were recorded within 30 days of acute PE. Of 125 patients followed at our center and included in the long-term analysis (median follow-up time 104, Q1-Q3 91-200, days), CTEPH was diagnosed in 2 (1.6%) patients. In one patient, CTEPH was most probably pre-existing, namely present already at the time of "acute" PE, based on hemodynamic and radiological findings. CTEPH was incident in the other patient. 24 (19.2%) patients reported persistent dyspnea, of whom 5 (4.0%) fulfilled the PPEI criteria. Death was recorded in 8 (6.4%) patients after a median of 591 (Q1-Q3; 517-710) days and no event was PE-related. One (0.8%) recurrent PE occurred. Conclusions: USAT rapidly reduced the mean pulmonary arterial pressure in selected intermediate-high and high-risk acute PE with a good safety profile. Only 4.0% patients had residual symptoms and right ventricular dysfunction over long-term follow-up. This data reassures USAT being an effective and safe option for acute PE also in terms of long-term outcomes.